Usługi mobilne w gospodarce elektronicznej - Pawełoszek, Ilona (Mobile services in electronic commerce, 2005)
The paper presents definition of mobile services, their types and possibilities of use in business processes such as: electronic shopping, information services, transactions, banking, advertisement, entertainments and communications. The concept of Electronic Mobile Commerce (m-commerce) - realized by means of mobile devices, has also been presented. The attempt to define the concept of mobile service was made, and the directions of future development were described.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Informatyka Ekonomiczna (8); 2005; nr 1094, s. 248-258